Impacts of major vehicular roads on urban landscape and urban growth in an arid region: A case study of Jiuquan city in Gansu Province, China. (April 2016) - Xie, Yuchu; Gong, Jie; Sun, Peng; Gou, Xiaohua; Xie, Yaowen
Abstract: Urbanization has brought about dramatic changes in the urban environment in China and its associated human population and transportation systems in recent years. However, urbanization in the oases of arid regions of China has been little studied and remains poorly understood. This paper aims to analyze spatiotemporal changes in an urban landscape along major vehicular road transects and compare the relationship between urban growth and transportation in Jiuquan, an oasis city in an arid region of China. We integrated remote sensing images, landscape metrics, and urban-rural gradient analysis to address these questions. The results showed that major vehicular roads stimulated Jiuquan's urban expansion, especially with regard to built-up land containing urban green land areas. Oasis urbanization not only increased landscape fragmentation and structural complexity, but also followed a linear branching, leapfrogging growth pattern characterized by "axial clumps" extending from downtown into rural areas along the road network. The primary source of urban land was not agricultural land, but unused land. These results also indicated that the transect approach implemented along representative roads was effective for studying the urbanization of oasis cities. Such an approach could be applied to master planning in similar oasis cities throughout arid China. Graphical abstract: Highlights: Spatiotemporal changes of urban landscape along typical vehicular road types were compared. Oasis urbanization increased landscape fragmentation and structural complexity. Urban expansion mainly occurred along the road network directions in arid China. Urbanization in arid regions was at the expense of unused land but not agricultural land.